HUMAN RESOURCE DEVELOPMENT STRATEGIES IN OIL PALM PLANTATION COMPANIES: A SWOT ANALYSIS APPROACH - Delyana Rahmawany Pulungan; Muhammad Ari Nasution; Junita Elisabeth; Dina Arfianti Saragih; Tifany Zia Aznur; Wahyudi Maherza; Suhendri Suhendri; Purjianto; Lendra Faqrurrowzi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
X is a company that has shifted its commodity from rubber to oil palm plantations. The company faces many challenges and difficulties in increasing the capacity and competence of its employees to support company productivity. The development of quality Human Resources (HR) can support various operational aspects. This study was conducted to analyze the factors influencing HR development at PT X using a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. This study uses the SWOT analysis method to evaluate internal and external factors influencing HR development. Data were obtained through questionnaires and employee interviews at the company. A descriptive approach was used to provide an in-depth overview of the condition of HR development in the company. This study was conducted from August to October 2024. The results show that the condition of Human Resources in the company is in quadrant I, which leads to an aggressive strategy of using strengths to seize opportunities. HR development strategies include increasing training and technical assistance, focusing on modern cultivation skills, forming work groups, and increasing land productivity for optimal and sustainable results